(untitled) (Global Journal of Science Frontier Research, 2017)
The Gulf of Khambhat, is united in a north-south orientation. Bhavnagar district is in Saurashtra region also known as Kathiawad, a part of Gujarat. Geographically the study area lies within the boundaries of Starting point N 21˚49’ 17.83” E 72˚15’ 21.03” Ending point 21˚49’ 46.92" N 72˚15’ 22.20" E. We have visited seven times during August’14 to February’15. Here we analysised heavy metals from sea water and Sediment.our main object is to prepare baseline study at ghed area.